2023
DOI: 10.3389/fpubh.2023.1122009
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of developmental disabilities in children and adolescents: A systematic umbrella review

Abstract: AimThe provisions of the United Nation's Sustainable Development Goals (SDGs) for disability-inclusive education have stimulated a growing interest in ascertaining the prevalence of children with developmental disabilities globally. We aimed to systematically summarize the prevalence estimates of developmental disabilities in children and adolescents reported in systematic reviews and meta-analyses.MethodsFor this umbrella review we searched PubMed, Scopus, Embase, PsycINFO, and Cochrane Library for systematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 30 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Intellectual and/or developmental disabilities (IDD) are disorders that present early in life and adversely affect the trajectory of the individual's physical, intellectual and/or emotional development 1 . Globally, an estimated 240 million children have developmental disabilities, 2 and about 2.6% (200 million) 3 of the world's population have an intellectual disability (IQ below 70). In Singapore, approximately 2.1% of students are estimated to have IDD, with 1 in 150 children diagnosed with autism spectrum disorder (ASD) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Intellectual and/or developmental disabilities (IDD) are disorders that present early in life and adversely affect the trajectory of the individual's physical, intellectual and/or emotional development 1 . Globally, an estimated 240 million children have developmental disabilities, 2 and about 2.6% (200 million) 3 of the world's population have an intellectual disability (IQ below 70). In Singapore, approximately 2.1% of students are estimated to have IDD, with 1 in 150 children diagnosed with autism spectrum disorder (ASD) 4 .…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that approximately 95% of autistic individuals live in low-middle income countries (LMICs). 3 , 4 Research has indicated a high number of children with neurodevelopmental disabilities in LMICs, specifically in sub-Saharan Africa, with the prevalence increasing. 4 The increasing numbers are attributed to improved diagnostic testing and the growing number of children surviving their first 5 years.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Research has indicated a high number of children with neurodevelopmental disabilities in LMICs, specifically in sub-Saharan Africa, with the prevalence increasing. 4 The increasing numbers are attributed to improved diagnostic testing and the growing number of children surviving their first 5 years. Moreover, Nigeria is one of the top ten countries with the highest prevalence of children with specific developmental disabilities under 5 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that 1 in 5 to 6 children has some DD, with an overall significant increase in the prevalence between 2009 and 2017 (Ricardo‐Garcell et al, 2022; Zablotsky et al, 2019). According to Olusanya et al the global prevalence of developmental intellectual disability was 3.1% (95% CI: 2.3–3.8), autism spectrum disorder 0.4% (95% CI: 0.3–0.5) and cerebral palsy 0.6% (95% CI: 0.5–0.6) (Olusanya et al, 2023). Those disabilities are more prevalent in those children with biological risk factors such as prematurity (Allotey et al, 2018; Heyne et al, 2018; Kerstjens et al, 2012; Schonhaut et al, 2015).…”
Section: Introductionmentioning
confidence: 99%